Accelerated weathering parameters for some aromatic engineering thermoplastics. (August 2019) - Pickett, James E.; Kuvshinnikova, Olga; Sung, Li-Piin; Ermi, Brett D.
Abstract: Samples of polycarbonate (PC), poly(butylene terephthalate) (PBT), a PC/PBT blend, and poly(styrene- co- acrylonitrile) (SAN), all containing 3% TiO2 (by mass), were exposed in the NIST (National Institutes of Standards and Technology) SPHERE (Simulated Photodegradation via High Energy Radiant Exposure) to determine the effects of UV intensity (irradiance), temperature, relative humidity (RH), and UV wavelength on yellowing and gloss loss. There was no effect of irradiance, such that the samples obeyed reciprocity and doubling the irradiance doubled the rate of degradation. The activation energy for yellowing was determined to be ≈ 20 kJ/mol for PC, PC/PBT, and SAN and ≈16 kJ/mol for PBT. The activation energy for gloss loss was determined to be 9–16 kJ/mol. Thus, a 10 °C increase in temperature results in a 20%–30% increase in degradation rate. There was no consistent effect of RH on PC or PC/PBT yellowing or gloss loss. SAN degraded rapidly under dry conditions but showed little effect for RH > 10%. PBT lost gloss more slowly under dry conditions but displayed no RH effect with yellowing. Shorter wavelength UV had a greater effect on PC/PBT compared to PC or PBT. Highlights: Weathering acceleration parameters were determined using the NIST SPHERE. PC, PBT, a PC/PBT blend, and SAN generally exhibited reciprocity. Activation energies determined from yellowing data were in the range of 16–21 kJ/mol. Little effect from humidity was observed with RH > 10%.